To solve the system of equations using the substitution method, we will first solve one of the equations for one variable and then substitute that expression into the other equation.
Given the system of equations:
- \( x - 2y = 3 \) (Equation 1)
- \( 4x - 8y = 12 \) (Equation 2)
Step 1: Solve Equation 1 for x
From Equation 1, we can solve for \( x \):
\[ x = 2y + 3 \]
Step 2: Substitute into Equation 2
Now, we substitute \( x \) from Equation 1 into Equation 2:
\[ 4(2y + 3) - 8y = 12 \]
Step 3: Simplify the equation
Now, expand and simplify:
\[ 8y + 12 - 8y = 12 \]
Notice that \( 8y - 8y \) cancels out:
\[ 12 = 12 \]
Step 4: Interpretation
The statement \( 12 = 12 \) is always true, which means that the original system of equations represents the same line. Thus, there are infinitely many solutions along that line.
Step 5: Expressing the solution
We can express the solution set in terms of one parameter. We already have:
\[ x = 2y + 3 \]
We can let \( y = t \), where \( t \) represents any real number.
Then we can express \( x \) as:
\[ x = 2t + 3 \]
Final Result
The solution to the system can be expressed in parametric form as:
\[ (x, y) = (2t + 3, t) \quad \text{for any real number } t. \]
This means that there are infinitely many solutions, all lying on the line defined by the original equations.